Saccadic Eye Movements in Elderly Depressed Patients With Suicidal Behaviors: An Exploratory Eye-Tracking Study - Barsznica, Yoan; Noiret, Nicolas; Lambert, Bérénice; Monnin, Julie; De Pinho, Claire; Hickel, Julia; Masse, Caroline; Richard-Devantoy, Stephane; Morgny, Cynthia; Bennabi, Djamila; Haffen, Emmanuel; Laurent, Eric; et al. (Frontiers in Psychology, 2021)
Suicidal behaviors (SB) are often associated with impaired performance on neuropsychological executive functioning (EF) measures that encourages the development of more specific and reliable tools. Recent evidences could suggest that saccadic movement using eye-tracking can provide reliable inform on EF in depressive elderly. The aim of this study was to describe oculomotor performances in elderly depressed patients with SB. To achieve this aim, we compared saccadic eye movements (SEMs) performances in elderly depressed patients (N=24) with SB and with no SB in prosaccade (PS) and antisaccade (AS) tasks under gap, step and overlap conditions. All participants also underwent a complete neuropsychological battery. Performances were impaired in SB patients who exhibited less corrected AS errors and longer time to correct them than patients with no SB. Moreover, both groups had similar performance for PS latencies and correct AS. These preliminary results suggested higher cognitive inflexibility in suicidal patients compared to non-suicidal. This inflexibility may explain the difficulty of the depressed elderly in generating solutions to the resurgence of suicidal ideation to respond adequately to stressful environments. The assessment of eye movement parameters in depressed elderly patients may be a first step in identifying high-risk patients for suicide.